Separate assessment of gluteus medius and minimus: B-mode or M-mode ultrasound? - Dieterich, Angela; Deshon, Louise; Pickard, Christine; Strauss, Geoff; McKay, Jan (Taylor and Francis, 2014)
The hip abductors gluteus medius (Gmed) and minimus (Gmin) differ slightly in function and how they are affected by hip joint pathology. A separate assessment of Gmed and Gmin is feasible by ultrasound (US) imaging. B-mode and M-mode US can be used to measure muscle thickness. Two B- and two M-mode scans of Gmed and Gmin thickness were taken in relaxation on 16 asymptomatic volunteers, repeated within 4 days on 11 subjects. Three types of intra-rater reliability of muscle thickness measurements were examined: (1) within-session reliability comparing two scans from the same session, (2) between-days reliability comparing thickness from two scanning occasion within 4 days and (3) reliability of taking thickness measurements by re-measuring the same US scans after 1 week. Thickness measurements on B- and M-mode images provided ICC3,1 >0.96 for within-session reliability. ICC3,k >0.89 for between-days reliability and ICC3,1 >0.85 for re-reading the same scans were estimated. Minimal detectable changes >1.0 mm within-session, >2.4 mm between-days and >1.7 mm for re-reading scans indicated that small thickness changes are not detectable. The investigation suggests a slight advantage for fascia recognition in B-mode and the advantage of visual control of muscle relaxation in M-mode.